Rice price stabilization in Bangladesh: Assessing the impact of public farm-gate and consumer price stabilization instruments on the overall grain market and developing orientations with a greater role for the private sector - Minot, Nicholas; Hossain, Shahadat; Kabir, Razin; Dorosh, Paul A.; Rashid, Shahidur (International Food Policy Research Institute, 2021)
Price instability is a fact of life. In a market economy, domestic prices change in response to changes in supply, consumer preferences, policy, world prices, and other factors. Crop prices tend to be particularly volatile because harvests occur only once or a few times per year and because the size of the harvest varies due to weather, prices, and other factors. For internationally-traded commodities, volatility in world prices can be another source of instability in domestic prices.